Microcephaly is associated with impaired educational development in children with congenital heart disease - Pfitzer, Constanze; Sievers, Laura K.; Hütter, Alina; Khaliq, Hashim-Abdul; Poryo, Martin; Berger, Felix; Bauer, Ulrike M. M.; Helm, Paul C.; Schmitt, Katharina R. L. (Frontiers in Cardiovascular Medicine, 2022)
Objectives This study aims to evaluate the school careers of patients with congenital heart disease (CHD) and microcephaly. Methods An exploratory online survey was conducted on patients from a previous study on somatic development in children with CHD in 2018 (n = 2818). A total of 750 patients participated in the online survey (26.6%). This publication focuses on 91 patients (12.1%) diagnosed with CHD and microcephaly who participated in the new online survey. Results Microcephaly was significantly associated with CHD severity (p < 0.001). Microcephalic patients suffered from psychiatric comorbidity two times as often (67.0%) as non-microcephalic patients (29.8%). In particular, the percentage of patients with developmental delay, intellectual debility, social disability, learning disorder, or language disorder was significantly increased in microcephalic CHD patients (p < 0.001). A total of 85.7% of microcephalic patients and 47.6% of non-microcephalic patients received early interventions to foster their development. The school enrollment of both groups was similar at approximately six years of age. However, 89.9% of non-microcephalic but only 51.6% of microcephalic patients were enrolled in a regular elementary school. Regarding secondary school, only half as many microcephalic patients (14.3%) went to grammar school, while the proportion of pupils at special schools was eight times higher. Supportive interventions, e.g., for specific learning disabilities, were used by 52.7% of microcephalic patients and 21.6% of non-microcephalic patients. Conclusion Patients with CHD and microcephaly are at high risk for impaired educational development. Early identification should alert clinicians to provide targeted interventions to optimize the developmental potential.